Interpellating children as imperial subjects: a content analysis of government-produced moral education textbooks (1903–1942). - Anzai, Shinobu (Paedagogica Historica, 2024)
The Meiji Restoration (1868) ended the Tokugawa Shogunate regime (1603–1867) and proclaimed the emperor as the supreme power of Japan. The Meiji emperor's reign began abruptly, requiring restoration leaders to construct an emperor-centred ideology of whole cloth. This ideology posited an eternal imperial Japan: a unique, tight-knit community of loyal subjects. To disseminate this ideology, the Meiji government introduced shūshin (moral teaching) into the elementary school curriculum, aiming to transform all Japanese children into imperial subjects. Drawing upon Louis Althusser's theory of interpellation via Ideological State Apparatuses (ISAs), this study reads textbook stories as an interpellation practice and shows how the government portrayed characters in the stories as "Unique and Absolute Subjects" of the ideology to persuade children to willingly subjugate themselves to national ideals. This study conducts direct textual and contextual analyses of kokutei shūshin-sho (government-produced moral training textbooks) produced between 1903 and 1942, with a special focus on the teaching unit of the kokka (state). Two themes – loyalty and the imperial family – dominate this unit. The analysis reveals that the stories created "targeted truth" by pruning away details of characters' real lives, putting a beautiful mask on them, and sometimes even re-inventing or mythologising them.